Ciberativismo e campo político brasileiro: uma reflexão crítica sobre as vicissitudes das lutas políticas na era do ciberespaço - Farias, Deusiney Robson de Araújo (2017)
Activism in cyberspace, also called cyberactivism, a transnational practice that puts us before invisible demands for techno excluded, and largely ignored by the political field, is presented as a solution to political problems, such as the collaborative public dialogue promotion and as online mobilization. In Brazil, the political struggles variations of recent years raise the following questions: what are the fundamental characteristics of activism in cyberspace and in the Brazilian political field? According to their characteristics, for what reasons do the demands and actions proposed by cyberactivists have little repercussion and support in the Brazilian political field and in society, often leading to temporary disappearance or at random? In response to these questions, we propose five hypotheses, namely: [1] political activism in cyberspace is part of an "activist protocampo"; [2] the hackeractivist has the potential to influence the political field through its actions of resistance; cyberactivists can simulate public opinion; The clickactivist or "like" activist is the maneuvering mass of the cyberactivist actions; [3] ciberactivism favors a much more alterity with the medium of communication and its connection links; [4] the political field is based on the blackmail game, characterized as its main conventional method of action / articulation; and [5] this form of activism provoked a political field reaction, which instrumented means capable of neutralizing actions in cyberspace and capitalizing on the results in favor of the image itself. The critical reflection on the Brazilian political and cybercultural reality aims at organizing a theoretical-methodological framework based on the deductive reasoning method, which is supported by two related symbolic models: [a] the political field as an autonomous microcosm, a socially structure based on a control and dispute system; and [b] activism in cyberspace, an emerging form of action with enormous political potential. Pierre Bourdieu's methodological view of relationally thinking about the object represented a fundamental part of our thesis. Likewise, the theoretical-epistemological framework formed in Brazil about activism in cyberspace contributed to the existing terms classification in the existing literature. Especially based on the concepts of Eugenio Trivinho, Jean Baudrillard, Fábio Malini, Henrique Antoun and Norberto Bobbio, we propose the concept of glocal activism, considering the global life organization modes added to the technomiditic local civilization arrangements resulted in a third social and political dimension, no longer local or global, but - just - glocal. This way, we conclude that, behind the political field visible power, there is an invisible power that acts through the blackmail game. In this dispute, hackeractivism has great potential to decrypt the existing game and eventually subvert the structures of power. This same action, however, makes us vulnerable to advanced digital technology, historically reinforcing the glocal phenomenon as an inexorable existential condition